Endometrial whole metabolome profile at the receptive phase: influence of Mediterranean Diet and infertility - Molina, Nerea M.; Jurado-Fasoli, Lucas; Sola-Leyva, Alberto; Sevilla-Lorente, Raquel; Canha-Gouveia, Analuce; Ruiz-Durán, Susana; Fontes, Juan; Aguilera, Concepción M.; Altmäe, Signe (Frontiers in Endocrinology, 2023)
Several metabolite classes have been identified in human endometrium, including lipids, nucleotides, amino acids, organic acids, and sugars. The first studies suggest the importance of metabolites in endometrial functions, as imbalance in uterine metabolites has been associated with low implantation rate and endometriosis. Nevertheless, most of studies have put emphasis on specific metabolite classes, and we lack the knowledge of the whole metabolome composition in human uterus. Further, a healthy dietary pattern has been shown to potentially protect against different endometrial dysfunctions and is a potential modulator of metabolomic composition and, consequently, the intrauterine microenvironment. The Mediterranean Diet (MD), characterized by a high intake of fruits, vegetables, cereals, nuts, legumes, fish, and olive oil, and a low consumption of meat, dairy products, and processed foods, has been associated with a wide range of benefits for health. Indeed, the MD pattern has displayed a beneficial role in endometriosis management and fertility; however, the relationship between the MD and the endometrial metabolome is still unknown. In our study, we set out to analyze receptive-phase endometrial metabolome profiles among women with infertility and their associations with MD. We provide the whole metabolome profile of the endometrium, where 925 different metabolites were identified. Among these metabolites, lipids comprised the largest part, where polyunsaturated fatty acids (PUFAs) prevailed. Our main results support that women with endometriosis and recurrent implantation failure displayed lower levels of PUFAs compared to women with male factor and unexplained infertility (i.e., no clear endometrial alterations), identifying a metabolome profile associated with infertility diagnoses where altered endometrial functions are suspected. Moreover, MD adherence seemed to be associated with the endometrial metabolomic profile in a manner dependent on the health status of the uterus. These study findings help to understand the molecular background of female infertility and lead to identification of potential molecular biomarkers and possibilities for modulation of endometrial microenvironment and, thereby, endometrial functions involved in embryo implantation and infertility.